First‐in‐human, double‐blind, placebo‐controlled, single‐dose escalation study of aducanumab (BIIB037) in mild‐to‐moderate Alzheimer's disease. Issue 3 (20th June 2016) - Ferrero, James; Williams, Leslie; Stella, Heather; Leitermann, Kate; Mikulskis, Alvydas; O'Gorman, John; Sevigny, Jeff
Abstract: Introduction: Aducanumab (BIIB037), a human monoclonal antibody selective for aggregated forms of amyloid beta, is being investigated as a disease‐modifying treatment for Alzheimer's disease (AD). Methods: This randomized, double‐blind, placebo‐controlled single ascending‐dose study investigated the safety, tolerability, and pharmacokinetics (PK) of aducanumab in patients with mild‐to‐moderate AD. Eligible patients were sequentially randomized 6:2 to aducanumab (0.3, 1, 3, 10, 20, 30, and 60 mg/kg) or placebo. Results: The primary outcome was safety and tolerability. Doses ≤30 mg/kg were generally well tolerated with no severe or serious adverse events (SAEs). All three patients who received 60 mg/kg aducanumab developed SAEs of symptomatic amyloid‐related imaging abnormalities, which completely resolved by weeks 8–15. Aducanumab Cmax, AUC0–last, and AUCinf increased in a dose‐proportional manner. Discussion: In this single‐dose study, aducanumab demonstrated an acceptable safety and tolerability profile and linear PK at doses ≤30 mg/kg (clinicaltrials.gov NCT01397539 ).